KARAKTERISTIK UMUR DAN PARITAS IBU BERSALIN DENGAN PREEKLAMPSIA DI RSUD PURBALINGGA - Surtiningsih Surtiningsih; Hertianingsih Hertianingsih (Viva Medika, 2011)
In Indonesia preeclampsia-eclampsia is a disease in pregnancy who asks a huge toll on themother and baby. Unknown maternal mortality rate ranged from 9.8% - 25.5%, while infantmortality is even higher, which is 42.2% - 48.9% (Wikjosastro, 2005). Based on preliminarystudies conducted in hospitals Purbalingga data showed the incidence of preeclampsia in theyear 2008 as many as 61 cases (4.16%) of the 1513 deliveries and increased in 2009 to 73cases (4.58%) of the 1594 deliveries. And based on preliminary studies conducted inhospitals Banjarnegara preeclampsia data obtained in 2009 were 71 cases (3.46%) of the2051 deliveries. Interest to describe the characteristics of maternal age and parity withpreeclampsia in hospitals Purbalingga 2009. The research design used in this research isquantitative descriptive retrospective approach using population. Population birth motherswith preeclampsia who were treated in the hospital delivery room Purbalingga of 2009amounted to 73 respondents. Sample total sampling number of 73 respondents. Data fromPurbalingga Hospital Medical records in 2009. It consists of a variable that is characteristicfeatures of maternal preeclampsia (age and parity). Analysis of data using frequencydistribution. Characteristics of maternal age with the greatest preeclampsia at the age of 2035years with a percentage of 50.68%, and the smallest at age <20 years with the percentage of 10.96%. Characteristics of maternal parity with the parity multiparas biggestpreeclampsia (bore 2-5 times) with a percentage of 45.20% and the smallest at paritygrandemultipara (gave birth to 6 times or more) with a percentage of 20.55%. Keywords: Mother Maternity, age, parity